Lactobacillus fermentum species ameliorate dextran sulfate sodium-induced colitis by regulating the immune response and altering gut microbiota. (2nd November 2019) - Jang, You Jin; Kim, Woon-Ki; Han, Dae Hee; Lee, Kiuk; Ko, Gwangpyo
ABSTRACT: We evaluated immunometabolic functions of novel Lactobacillus fermentum strains (KBL374 and KBL375) isolated from feces of healthy Koreans. The levels of inflammatory cytokines, such as interleukin (IL)-2, interferon-γ, IL-4, IL-13, and IL-17A, were decreased, and that of the anti-inflammatory cytokine IL-10 was increased, in human peripheral blood mononuclear cells (PBMCs) treated with the L. fermentum KBL374 or KBL375 strain. When these strains were orally administered to mice with dextran sulfate sodium (DSS)-induced colitis, both L. fermentum KBL374 and KBL375 showed beneficial effects on body weight, disease activity index score, colon length, cecal weight, and histological scores. Furthermore, both L. fermentum KBL374 and KBL375 modulated the innate immune response by improving gut barrier function and reducing leukocyte infiltration. Consistent with the PBMC data, both L. fermentum KBL374- and KBL375-treated DSS mice demonstrated decreased Th1-, Th2-, and Th17-related cytokine levels and increased IL-10 in the colon compared with the DSS control mice. Administration of L. fermentum KBL374 or KBL375 to mice increased the CD4+CD25+Foxp3+Treg cell population in mesenteric lymph nodes. Additionally, L. fermentum KBL374 or KBL375 administration reshaped and increased the diversity of the gut microbiota. In particular, L. fermentum KBL375 increased the abundance of beneficial microorganisms, such as Lactobacillus spp. and Akkermansia spp. Both L. fermentum KBL374 and KBL375 may alleviate inflammatory diseases, such as inflammatory bowel disease, in the gut by regulating immune responses and altering the composition of gut microbiota.